Paget's disease of bone: A rare case report - Mohsin M Tak; Altaf H Chalkoo; Tauseefa Jan (Wolters Kluwer Medknow Publications, 2020)
Paget's disease of bone (PDB) is a localized bone remodeling disorder that is chronic, non-inflammatory.. It is also known as "osteodystrophia deformans" as described by Sir James Paget. PDB is the second most common bone disease after osteoporosis. This disease is found to be relatively more common in older people, occurs in approximately 3-4% of the population aged over 50 years with a slight male gender predilection. Jaw involvement is seen with the ratio of maxilla to mandible 2:1.